Variational method for the solution of problems of transmission with the principal conjugation condition - Komarenko, A. N.; Trotsenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove the existence of a solution of a variational minimax problem that is equivalent to the problem of transmission. We propose an algorithm for the construction of approximate solutions and prove its convergence.